Pep4-dependent microautophagy is required for post-ER degradation of GPI-anchored proteins. Issue 1 (2nd January 2022) - Lemus, Leticia; Goder, Veit
ABSTRACT: Clearance of misfolded proteins from the secretory pathway often occurs soon after their biosynthesis by endoplasmic reticulum (ER)-associated protein degradation (ERAD). However, certain types of misfolded proteins are not ERAD substrates and exit the ER. They are then scrutinized by ill-defined post-ER quality control (post-ERQC) mechanisms and are frequently routed to the vacuole/lysosome for degradation. Glycosylphosphatidylinositol-anchored proteins (GPI-APs) constitute a class of proteins of the secretory pathway that mostly depends on post-ERQC. How misfolded GPI-APs are detected, transported to the vacuole/lysosome and taken up by this organelle was poorly defined. Originating from the intriguing observation that several misfolded GPI-APs accumulate in the yeast vacuolar membrane in the absence of the major vacuolar protease Pep4, we designed an unbiased genome-wide screen in yeast and followed the trafficking of the misfolded fluorescent GPI-AP Gas1* from the ER to the vacuolar lumen. Our results reveal that post-ERQC of GPI-APs is linked with a novel type of microautophagy.